PENGARUH PEMBERIAN PUPUK UREA DAN PUPUK ORGANIK CAIR SAMPAH KOTA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Cik Zulia; Deddy Wahyudin Purba; Harmi Dedi Hirawan (Bernas : Jurnal Penelitian Pertanian, 2017)
The research plan was conducted at the Experimental Garden of the University of Asahan Faculty of Agriculture, with flat topography and high place ± 15 m asl. The research plan is carried out from February to April 2017. The materials used in this research are General varieties of lettuce seeds, urea fertilizer, liquid organic fertilizer of urban trash, water, envelopes, label paper, coconut bark as roof shade nursery, insecticide materials Active Deltamethrin 25 g / l (Decis 2.5 EC 0.25 - 0.5 ml / l), Mankozed 80 WP (Dithane M-45) active material fungicide, scales and other materials supporting the conduct of this study, The tool used in this research is hoe, gembor, meter, handsprayer, calculator, scales, planimeter, wire as bamboo bamboo binder and other supporting tools in the implementation of this research. This research was arranged based on Factorial Randomized Block Design (RAK) with 2 treatment factors and 3 replications. The first factor was Urea fertilizer with 4 levels: U0 = 0 g/plot, U1 = 5 g/plot and U2 = 10 g/plot and U3 = 15 g/plot. The second factor is the provision of liquid organic fertilizer of municipal solid waste consisting of 3 levels ie K0 = 0 ml/plot, K1 = 0,15 ml/plot and K2 = 0,30 ml/ plot. The results showed that urea fertilizer gave significant effect on the parameters of plant height, number of leaves, production per plant and production per plot, with best dose of U3 treatment (15 g/plot). Provision of liquid organic fertilizers of urban solid waste showed a significant effect on the parameters of plant height, number of leaves, production per production plant per plot, with the best dose on K2 treatment (0.30 ml / plot). The interaction between treatment of urea fertilizer and liquid organic fertilizer of urban solid waste did not show any significant effect on growth and production of lettuce.